2014
DOI: 10.1021/co400157m
|View full text |Cite
|
Sign up to set email alerts
|

Ag–ZnO Nanoreactor Grown on FTO Substrate Exhibiting High Heterogeneous Photocatalytic Efficiency

Abstract: This Research Article reports an unusually high efficiency heterogeneous photodegradation of methyl orange (MO) in the presence of Ag nanoparticle-loaded ZnO quasi-nanotube or nanoreactor (A-ZNRs) nanocatalyst grown on FTO substrate. In typical process, photodegradation efficiency of as high as 21.6% per μg per Watts of used catalyst and UV power can be normally obtained within only a 60-min reaction time from this system, which is 10(3) order higher than the reported results. This is equivalent to the turnove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…ZnO an inexpensive, nontoxic and easily available Lewis acid is a good example of metal oxide which has widely been used as a catalyst in various chemical transformations and is widely studied. Tuning the performance and activity of nanocrystalline ZnO by doping it with Ag is of current research interest …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ZnO an inexpensive, nontoxic and easily available Lewis acid is a good example of metal oxide which has widely been used as a catalyst in various chemical transformations and is widely studied. Tuning the performance and activity of nanocrystalline ZnO by doping it with Ag is of current research interest …”
Section: Resultsmentioning
confidence: 99%
“…Ghosh et al observed that NPs doped or supported with another metal boosted the catalytic efficiency to great extent due to synergistic effect . Literature reports revealed that noble metal NPs such as silver supported on other materials showed incredible applications in catalysis …”
Section: Introductionmentioning
confidence: 99%
“…In addition, attempts have also been made to design ZnO photocatalysts with effective charge separation and storage of the photoexcited charges. Recently, it has been shown that loading of silver nanoparticles (AgNPs) on ZnO surface can reduce photocorrosion, improve absorption of visible light, and increase the photocatalytic efficiency of ZnO.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] It is noteworthy that the doping technique is an alternative way to ease the band gap tuning of the semiconductor. To validate the correlation between the band gap alignment and devices performance, in present work, we introduced a facile synthesis method to alter the single band structure to interface induced band gap states by controlling the CdS deposition cycle via successive ionic layer adsorption and reaction (SILAR).…”
Section: Introductionmentioning
confidence: 99%